2018
DOI: 10.1016/j.chempr.2018.08.038
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphorus Lewis Super Acid: η5-Pentamethylcyclopentadienyl Phosphorus Dication

Abstract: An h 5 -pentamethylcyclopentadienyl phosphorus dication [(h 5 -Cp*)P] 2+ has been synthesized and characterized, representing an h 5 -cyclopentadienyl-bound phosphorus species. The reactivity of the dication reveals its phosphorus-centered Lewis super acidity and interesting hapticity shifts of the cyclopentadienyl ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 66 publications
2
22
0
7
Order By: Relevance
“…The modeled dismutation of dicationic 6 to hypothetical [Sr(HMB) 2 ] 2+ and [Sr(oDFB) 8 ] 2+ was shown to be unfavorable in D R G , underlining the stability of this unique mixed hard/so coordination environment. The so generated dicationic AE arene complexes are unprecedented and show high and hard Lewis acidities in line with other Lewis superacidic, neutral, 32 mono-33 and dicationic 31,34 main-group Lewis acids published in recent years.…”
Section: Chemical Science Edge Articlesupporting
confidence: 74%
“…The modeled dismutation of dicationic 6 to hypothetical [Sr(HMB) 2 ] 2+ and [Sr(oDFB) 8 ] 2+ was shown to be unfavorable in D R G , underlining the stability of this unique mixed hard/so coordination environment. The so generated dicationic AE arene complexes are unprecedented and show high and hard Lewis acidities in line with other Lewis superacidic, neutral, 32 mono-33 and dicationic 31,34 main-group Lewis acids published in recent years.…”
Section: Chemical Science Edge Articlesupporting
confidence: 74%
“…The attempt to synthesize toluene‐free [Cp*As][B(C 6 F 5 ) 4 ] 2 akin to the [CpSn] + by performing the reaction of Cp*AsCl 2 with 2 equivalents of [Et 3 Si(tol)][B(C 6 F 5 ) 4 ] in pentane gave 1 as the only As‐containing product. Similar interactions to aromatic solvents in the solid state have been reported for (C 6 F 5 ) 3 Al(tol), [Et 3 Si(tol)][B(C 6 F 5 ) 4 ], and [(η 5 ‐Cp*)P(tol)][B(C 6 F 5 ) 4 ] 2 , consistent with the high Lewis acidity of 2 . It is noteworthy that 2 represents the first structurally characterized arsenic compound with a true η 5 ‐Cp‐type ligand, although a computational study demonstrating that [(Cp)(Cp*)As] + cation contains η 5 ‐Cp‐type ligands has been reported …”
Section: Figuresupporting
confidence: 79%
“…We recently synthesized a toluene coordinated η 5 ‐pentamethylcyclopentadienyl phosphorus dication [(η 5 ‐Cp*)P(tol)] 2+ featuring Lewis super acidity owing to low‐lying LUMOs on the dicationic P center (Figure c) . Seeking to develop related LSAs, in the present work, we report the synthesis, characterization, and reactivity of an arene‐stabilized η 5 ‐pentamethylcyclopentadienyl (Cp*) arsenic dication [(η 5 ‐Cp*)As(tol)] 2+ (Figure c).…”
Section: Figurementioning
confidence: 99%
“…In conclusion, we were able to isolate and fully characterise the first transition metal complexes bearing pentaphosphole (cyclo-P 5 R) ligands. Silylation and methylation of [Cp*Fe(h 5 -P 5 )] (1) afforded the respective products [Cp*Fe-(h 5 bears the parent cyclo-P 5 H ligand. Crystallographic characterisation of these compounds revealed that the P 5 R unit, in contrast to earlier computational predictions, [18] shows a slight envelope structure, which we attribute to the coordination to the {Cp*Fe} + fragment.…”
Section: Resultsmentioning
confidence: 99%